Military Forts of the Kachwaha Kings of Jaipur: जयपुर के कच्छवाहा राजाओं के सैन्य दुर्ग - Mahawar, Mangilal; Rathore, Suman (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In ancient and medieval India, forts were considered essential for military security and defense management. The Rajput princely states of Rajasthan also regarded forts as the most important means of ensuring their protection. For this reason, Rajasthan is often referred to as the land of forts or strongholds. It was rare to find a state in this region that did not possess a small or large fort, as the very existence of a kingdom depended on the defense provided by its forts. The fall of a fort was regarded as a symbol of the destruction of the state itself. Consequently, the capital of every state here was necessarily established within a fort. In this context, the Kachwaha rulers of Jaipur, including Man Singh, Mirza Raja Jai Singh, Sawai Jai Singh II, Madho Singh, and Ram Singh, carried out numerous constructions works and built powerful forts to ensure the security of their kingdom. The forts of the Jaipur state were not only symbols of military strength but also served as the foundations of administrative, social, economic, and cultural structures. The Kachwaha capital, Jaipur, has been renowned worldwide for its grandeur, architectural excellence, military forts, and rich cultural traditions. Surrounded by several small and large forts such as Amer, Jaigarh, Nahargarh, and Amagarh, these strongholds have served as vigilant guardians of Jaipur for centuries. These forts are not merely piles of stones; rather, they stand as living testimonies to struggle, military strategy, remarkable architecture, and the courage of the Kachwaha Rajputs. Abstract in Hindi Language: प्राचीन एवं मध्यकालीन भारत में सैन्य सुरक्षा प्रबंधन में दुर्गों को अति आवश्यक माना गया। राजस्थान की राजपूत रियासतों ने भी अपनी सुरक्षा के लिए दुर्गों को सर्वाधिक महत्वपूर्ण उपाय माना। इसी कारण राजस्थान को गढ़ अथवा दुर्गों का प्रदेश भी कहा जाता है। यहां शायद ही कोई ऐसा राज्य रहा हो जिसके पास छोटा अथवा बड़ा दुर्ग या गढ़ ना रहा हो क्योंकि राज्य का अस्तित्व दुर्ग रक्षा पर ही निर्भर करता था। दुर्ग का पतन राज्यों के अस्तित्व के नाश का प्रतीक माना जाता था। यही कारण है कि यहां प्रत्येक राज्य की राजधानी अनिवार्य रूप से दुर्ग में ही हुआ करती थी। इसी क्रम में जयपुर के कच्छवाहा राजाओं जिनमें मानसिंह, मिर्जा राजा जयसिंह, सवाई जयसिंह द्वितीय, माधोसिंह, रामसिंह आदि ने जयपुर में अनेक निर्माण कार्य करवाते हुए अपने राज्य को सुरक्षा प्रदान करने के लिए शक्तिशाली दुर्गों का निर्माण करवाया। जयपुर रियासत के दुर्ग न केवल सैन्य शक्ति के प्रतीक रहे है, अपितु प्रशासनिक, सामाजिक, आर्थिक एवं सांस्कृतिक संरचना के आधार स्तंभ भी रहे। कच्छवाहों की राजधानी जयपुर अपनी भव्यता, स्थापत्य कला, सैन्य दुर्गों एवं सांस्कृतिक परंपराओं के कारण दुनियाभर में प्रसिद्ध रही है। इस राज्य के चारों ओर बहुत से छोटे-बड़े दुर्ग जिनमें आमेर, जयगढ़, नाहरगढ़, आमागढ़ आदि प्रमुख किले शताब्दियों से जयपुर के सुरक्षा प्रहरियों की भूमिका निभाते आए हैं। ये दुर्ग केवल पत्थरों का ढेर नहीं, बल्कि संघर्ष, सैन्य कूटनीति, बेजोड़ स्थापत्य कला और कच्छवाहा राजपूतों के साहस की जीवित मिसालें हैं। Keywords: कच्छवाहा वंश, दुर्ग, सुरक्षा, आमेर, जयगढ़, तोपखाना